2011
DOI: 10.1155/2011/837091
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Ag-Doped BaTiO3 Conductive Powders

Abstract: BaTiO 3 powders doped with Ag at different Ag/Ba molar ratios were prepared by sol-gel method. The resistivity reached the lowest point of 5.644 Ω·m when Ag concentration was 0.10 at% and the powders were calcined for two times at 800• C and 500 • C. XRD and FTIR investigations showed that no new substance was formed after the doping and calcining process, but the particle size and the strength of Ti-O bond in modified BaTiO 3 crystal cell all changed. The conductivity of Ag-doped BaTiO 3 powders with differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Thus, the low sintering temperature of the glass flux added BaTiO 3 was attributed to the loose network shown by the IR study since loose network glass usually possess a low melting nature. The Ti-O vibration and characteristic peak of BaTiO 3 is consistent with reported work elsewhere [18,19]. Fig.…”
Section: Resultssupporting
confidence: 91%
“…Thus, the low sintering temperature of the glass flux added BaTiO 3 was attributed to the loose network shown by the IR study since loose network glass usually possess a low melting nature. The Ti-O vibration and characteristic peak of BaTiO 3 is consistent with reported work elsewhere [18,19]. Fig.…”
Section: Resultssupporting
confidence: 91%
“…The area elemental mapping was carried out to further reveal the composition of P-BTO nanoparticles, demonstrating that Ba, O, C, and Ti were distributed uniformly in the whole matrix of P-BTO (Figure 2g). Fourier transform infrared (FT-IR) spectroscopy showed that barium titanate exhibited absorption bands around 550 cm −1 (Figure 2h, dark green dotted line), 36 which was displayed in both of the FT-IR spectra peaks of barium titanate and P-BTO nanoparticles. The characteristic peaks of DSPE-PEG 2000 were O−CH 2 (1113 cm −1 ; Figure 2h, light green dotted line), NH-CO (1669 cm −1 ; Figure 2h, purple dotted line), and −CH 2 (2917 cm −1 ; Figure 2h, black dotted line), 37 which could be observed from the FT-IR peaks of DSPE-PEG 2000 and P-BTO nanoparticles, suggesting that the BTO nanoparticles were successfully coated with DSPE-PEG 2000 .…”
Section: Resultsmentioning
confidence: 99%
“…However, in general, the vibration modes in the 400–600 cm –1 range correspond to the infrared absorption region. There are two strong absorption bands that fall in this region at 545 and 655 cm –1 due to vibrations caused by bending and stretching of Ti–O–Ti bond in [TiO 6 ] 2– 14 . The 655 cm –1 band has shifted to the high frequencies in BTY 2 (688 cm –1 ), BTY 10 (661 cm –1 ), and BTY 10 Nb 10 (671 cm –1 ).…”
Section: Resultsmentioning
confidence: 99%
“…There are two strong absorption bands that fall in this region at 545 and 655 cm -1 due to vibrations caused by bending and stretching of Ti-O-Ti bond in [TiO 6 ] 2-. 14 The 655 cm -1 band has shifted to the high frequencies in BTY 2 (688 cm -1 ), BTY 10 (661 cm -1 ), and BTY 10 Nb 10 (671 cm -1 ). Structural deviation in the BT is responsible for this shift.…”
Section: Ftir Spectramentioning
confidence: 97%